2008
DOI: 10.1007/s00268-008-9661-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sildenafil Citrate on Ischemic Colonic Anastomotic Healing in Rats: Its Relationship Between Nitric Oxide and Oxidative Stress

Abstract: Our results suggest that sildenafil citrate may affect ischemic anastomotic healing due to its possible effects on nitric oxide metabolism and lipid peroxidation. However, functional implication of this agent further needs to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…More recently, it has been used in the diseases induced by hypoxia, such as pulmonary hypertension, chronic heart failure and indomethacin-induced gastropathy, due to its features of vasodilation and the regulation of blood flow [8,10,18]. Additionally, there has been research that shows its protective effects due to its anti-oxidant features against IRD in tissues such as the heart, liver, lungs, kidney, colon and testicle [6,8,9,19,20]. It has been asserted that sildenafil regulates blood flow by increasing nitric oxide production, and decreases FOR by inhibiting leucocyte infiltration and adhesion [9,10].…”
Section: Discussionmentioning
confidence: 98%
“…More recently, it has been used in the diseases induced by hypoxia, such as pulmonary hypertension, chronic heart failure and indomethacin-induced gastropathy, due to its features of vasodilation and the regulation of blood flow [8,10,18]. Additionally, there has been research that shows its protective effects due to its anti-oxidant features against IRD in tissues such as the heart, liver, lungs, kidney, colon and testicle [6,8,9,19,20]. It has been asserted that sildenafil regulates blood flow by increasing nitric oxide production, and decreases FOR by inhibiting leucocyte infiltration and adhesion [9,10].…”
Section: Discussionmentioning
confidence: 98%
“…However, unlike us, they evaluated the oxidant/antioxidant parameters in only tissue levels, whereas we evaluated them in both tissues and serum. Similarly, Uzun et al [34] Ulus Travma Acil Cerrahi Derg, September 2014, Vol. 20, No.…”
Section: Discussionmentioning
confidence: 99%
“…[23,[30][31][32][33][34]46,47] Histopathological evaluations of those studies also demonstrated the positive effects of various dosages of sildenafil administration (range 2±25 mg/kg) in decreased inflammation scores.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…It is also used in the treatment of the age-related diseases. [31,32]. It has been shown that inhibin-B is the only physiologically important hormone in rats and in men, [33].…”
Section: Discussionmentioning
confidence: 99%